La construction de la tour Saint-Laurent du palais des Papes (1353-1357) : nouveaux regards sur un chantier - Philippe Bernardi; Andreas Hartmann-Virnich; Dominique Vingtain (Archéologie Médiévale)
The opportunity to study the Saint-Laurent tower of the Avignon Palais des Papes (1353-1357), undertaken between 1997 and 1999 in the context of a collective research project, was provided by restoration work. This project has enabled the team to retrace and to characterize the functioning of one of the major building programmes of its period in the south of France. The enquiry, primarily based on the joint analysis of archives and elevation surveys, highlights the organisation and implementation of the building project within a tight chronological framework specified through reinterpretation of the accounts, and the main stakes of this approach: the organisation of the cutting and supplying of building stone, the construction strategies, the types of scaffolding, arch templates and other ephemeral installations, as well as repentances that evoke a lively picture of day to day life on a building site. The example of the Saint-Laurent tower illustrates the complementarity of the study of archival sources and standing building studies in the context of an ambitious architectural project, a princely undertaking benefitting from exceptional financial support.